The diagnostic performance of rapid diagnostic tests and microscopy for malaria diagnosis in eastern Sudan using a nested polymerase chain reaction assay as a reference standard. (23rd July 2019) - Abdalla, Zakya A; Rahma, NourElhouda A; Hassan, Elhashimi E; Abdallah, Tajeldin M; Hamad, Hadeel E; Omer, Samia A; Adam, Ishag
Abstract: Background: Accurate diagnosis of malaria infection is essential for successful control and management of the disease. Both microscopy and rapid diagnostic tests (RDTs) are recommended for malaria diagnosis, however, RDTs are more commonly used. The aim of the current study was to assess the performance of microscopy and RDTs in the diagnosis of Plasmodium falciparum infection using a nested polymerase chain reaction (PCR) assay as the gold standard. Methods: A cross-sectional study was carried out in Kassala Hospital, eastern Sudan. A total of 341 febrile participants of all ages were recruited. Blood specimens were collected and malaria testing was performed using an RDT (SD Bioline Malaria Ag Pf), microscopy and nested PCR. The sensitivity, specificity, positive and negative predictive values (PPV and NPV, respectively) of microscopy and the RDT were investigated. Results: The prevalence of P. falciparum malaria infections in this study was 22.9%, 24.3% and 26.7% by PCR, microscopy and RDT, respectively. Compared with microscopy, the RDT had slightly higher sensitivity (80.7% vs 74.3%; p=0.442), equivalent specificity (89.3% vs 90.4%), a similar PPV (69.2% vs 69.8%) and a higher NPV (94.0% vs 92.2%). Conclusions: The diagnostic performance of the RDT was better than that of microscopy in the diagnosis of P. falciparum malaria when nested PCR was used as the gold standard.